An Efficient Operations and Management Challenges of Next Generation Network (NGN) (Global Journal of Computer Science and Technology, 2014)
Next Generation Network (NGN) is envisioned to be an inter-working environment of heterogeneous networks of wired and wireless access networks, PSTN, satellites, broadcasting, etc., all interconnected through the service provider2019;s IP backbone and the Internet. NGN uses multiple broadband, QoS-enabled transport technologies and servicerelated functions independent from underlying transportrelated technologies. The operations and management of such interconnected networks are expected to be much more difficult and important than the traditional network environment. In this paper, we present an overview of the current status towards the management of NGN and discuss challenges in operating and managing NGN. We also present the operations and management requirements of NGN in accordance with the challenges and verified two routing protocols for QOS support and providing security using caesarchiper encryption/decryption in Ad-hoc networks and also provide QOS for wired networks by AQM techniques and simulated results of AQM, Routing protocols using NS-2 and Encryption/Decryption using Matlab tools.
Keywords: QOS AQM; NGN; red and drop tail